2022
DOI: 10.1126/sciadv.abo0517
|View full text |Cite
|
Sign up to set email alerts
|

Chaperoning of the histone octamer by the acidic domain of DNA repair factor APLF

Abstract: Nucleosome assembly requires the coordinated deposition of histone complexes H3-H4 and H2A-H2B to form a histone octamer on DNA. In the current paradigm, specific histone chaperones guide the deposition of first H3-H4 and then H2A-H2B. Here, we show that the acidic domain of DNA repair factor APLF (APLF AD ) can assemble the histone octamer in a single step and deposit it on DNA to form nucleosomes. The crystal structure of the APLF AD -histone octamer complex sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Experimental structural biology would be required to confirm these models. The ability of a peptide to act as a chaperone for an intact histone octamer has been observed before for the APLF peptide ( 28, 30 ). The MIER1:octamer complex would appear to allow initial binding of DNA to the H3:H4 dyad position.…”
Section: Discussionsupporting
confidence: 53%
“…Experimental structural biology would be required to confirm these models. The ability of a peptide to act as a chaperone for an intact histone octamer has been observed before for the APLF peptide ( 28, 30 ). The MIER1:octamer complex would appear to allow initial binding of DNA to the H3:H4 dyad position.…”
Section: Discussionsupporting
confidence: 53%
“…While H2A­ H2B may be released directly to the assembling nucleosome, it could also be released to another H2A-H2B chaperone. Candidate chaperones include Nap1, FACT, or APLF (Chen et al 2016; Liu et al 2020; Corbeski et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This region has been reported to be involved in the binding to histones. 33 Importantly, our data using APLF showed that the lack of the acidic domain abolished the formation of stable synaptic events (Figure 2D). This observation contrasts with the results obtained for wild-type APLF (Figure 1E).…”
Section: The Aplf C-terminal Acidic Domain Is Critical For Dna End Br...mentioning
confidence: 76%
“…18,30 APLF also interacts with poly(ADP-ribose) (PAR) via two PAR-binding zinc finger (PBZ) domains 31,32 and binds histones through its C-terminal disordered acidic region. 33,34 APLF facilitates NHEJ, at least in part, by promoting the formation and/or the stability of complexes between Ku and X4-LIG4 on the DNA, which are required for an efficient ligation. 25 Besides protein factors, accumulating evidence shows that some long non-coding RNAs (lncRNAs) regulate DNA damage response pathways.…”
Section: Introductionmentioning
confidence: 99%